1984
DOI: 10.1159/000225851
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dihydrofolate Reductase and Cell Growth by Antifolates in a Methotrexate-Resistant Cell Line

Abstract: The structural features and lipid solubility of four different classes of antifolate compounds were compared for their inhibition of dihydrofolate reductase (DHFR) and growth in a normal and methotrexate (MTX)-resistant 3T6 mouse cell line. All of the compounds have been shown previously to have antifolate activity. The resistant cell line has a 7-fold increase in DHFR activity with normal transport, but an altered affinity for MTX. All the antifolates were equally effective in inhibiting DHFR and growth in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The structural requirements for potential DHFR inhibitors are summarized in recent review articles. The availability of high resolution crystal structures of Pneumocystis carinii DHFR and human DHFR has provided impetus in the use of rational drug design techniques for the development of highly potent and specific DHFR inhibitors. , Thus, DHFR antagonists have been extensively studied and are currently used for the treatment of cancer, , psoriasis, autoimmune diseases, malaria, bacterial and fungal infections, and infections by opportunistic microorganisms associated with AIDS. Such inhibitors have been classified according to their structures, classical and nonclassical. The former have a structure similar to folate, where they possess a ring which is generally a pteridine connected to an aryl group and a moiety of glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…The structural requirements for potential DHFR inhibitors are summarized in recent review articles. The availability of high resolution crystal structures of Pneumocystis carinii DHFR and human DHFR has provided impetus in the use of rational drug design techniques for the development of highly potent and specific DHFR inhibitors. , Thus, DHFR antagonists have been extensively studied and are currently used for the treatment of cancer, , psoriasis, autoimmune diseases, malaria, bacterial and fungal infections, and infections by opportunistic microorganisms associated with AIDS. Such inhibitors have been classified according to their structures, classical and nonclassical. The former have a structure similar to folate, where they possess a ring which is generally a pteridine connected to an aryl group and a moiety of glutamate.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies using metoprine indicated that the activation of the histaminergic system in the CNS affects a wide variety of brain functions such as antinociception [79], suppression of energy intake [80], hyperglycaemic action [81], improvement of cognitive function [82], antiepileptic effect [83,84,85], and attenuation of methamphetamine-induced behavioural abnormalities [86]. However, metoprine can also inhibit mammalian dihydrofolate reductase (EC 1.5.1.3) and decrease cellular folate metabolism, resulting in the attenuation of cell growth [87,88]; therefore, it cannot be ruled out that the low specificity of metoprine affected the results. Another HNMT inhibitor, SKF91488, developed by Beaven et al can specifically inhibit the enzymatic activity devoid of histamine receptor agonist activity [89].…”
Section: Pharmacological Analysis Using Hnmt Inhibitorsmentioning
confidence: 99%
“…Because of their distinct pharmacological and physicochemical properties compared to MTX, new antifolate compounds are being investigated for use against MTX-resistant cells (Burchenal et al 1952;Mishra et al 1973;Ho et al 1972;Nichol et al 1977). The use of these classes of analogs to increase selectivity and overcome the issue of MTX-resistant cells has gotten a lot of attention (Hamrell 1984). B-cell lymphoma-2 (BCL-2) is the name given to an unidentified gene found in follicular lymphoma (Tsujimoto et al 1985).…”
Section: Introductionmentioning
confidence: 99%